New approachesto the study of the History of Women: between genders, equality and freedom: Review of Ancona, R.; Tsouvala, G. (eds.) New Directions in the Study of Women in the Greco-Roman World(2021) - Gontijo Leite, Priscilla; Pelluci Duarte Mortoza, Marina (Revista Archai, 2023)
Review of Ancona, R.; Tsouvala, G. (eds.) New Directions in the Study of Women in the Greco-Roman World (2021)